AFR Modeling of EFI Engine Based on Engine Dynamics, Vehicle Dynamics, and Transmission System - Suroto Munahar; Muji Setiyo (Jurnal Teknik Mesin, 2017)
During this time, the AFR control systems on the Ligh Duty Vehicles (LDVs) generally only engage the engine condition, such as manifold pressure, engine speed. In fact, fuel consumption is not only influenced by the engine dynamics but also influenced by outside factors such as gear position (transmission) and vehicle speed. Therefore, this paper presents a simulation to control the Air to Fuel Ratio (AFR) on Electronic Fuel Injection (EFI) engine that accommodated engine dynamics, vehicle speed dynamics, and gear position dynamics (transmission). Fuzzy Logic Controller (FLC) was selected for AFR modeling because of the engine work in a non-linear condition. The simulation results show that the model developed is able to control the AFR on the vehicle speed changes. Even, the system is able to perform fuel cut-off at the time of deceleration from high speeds.